Depressive symptoms are associated with mortality among patients with hip fractures in Japan: a prospective cohort study - Saori Motegi; Satoshi Miyata; Takahiro Inui; Hironari Masuda; Keisuke Ishii; Yoshinobu Watanabe; Hirotaka Kawano (BMC Musculoskeletal Disorders)
Abstract Background Patients with hip fractures are increasing in Japan, and lack of activities due to the fractures can significantly affect their mental health. However, the association between depressive symptoms and mortality in patients with hip fractures remains unclear because of conflicting evidence. This study aimed to evaluate whether depressive symptoms in Japanese patients after hip fracture surgery affect patient survival rates. Methods Data were obtained from a cohort study on postoperative fragility fracture at the Teikyo University Hospital that included individuals who underwent hip fracture surgery between May 2018 and November 2020. Depressive symptoms were assessed using the postoperative Patient Health Questionnaire (PHQ)-9 score. Logistic regression analysis and the Cox proportional hazards model were used to analyze the effect of depressive symptoms on survival. Results In total, 175 patients were included, of whom 130 (76.2%) were female, with a mean age of 79.8 (± 10.3) years. A high PHQ-9 score was associated with worse 6-month survival (odds ratio 1.15 [1.05–1.27], p = 0.004; and hazard ratio 1.11 [1.00-1.23], p = 0.057). Conclusions Postoperative depressive symptoms are associated with worse prognosis in patients with hip fractures.